The design of educational materials for teaching the most common religions to students in their final year of primary school: a cross-curricular approach of religious studies and music, through the use of augmented reality - Karamouzis, Polikarpos (Online - Heidelberg journal of religions on the internet, 2016)
The aim of this research is to establish whether teaching approaches based on the use of Augmented Reality (AR) facilitate deeper and more engaging learning. The religions of Christianity, Islam, Hinduism, Buddhism and their sacred musics were taught through an interdisciplinary methodology.Qualitative research was conducted with a sample of 34 final-year, Greek primary school students. The syllabus and teaching conditions were identical for all students. However, the experimental group was taught using educational materials designed on the Aurasma AR application. The research findings suggest that the use of AR supported deeper and more engaging learning, confirming the limited relevant findings in international literature.